Digital Innovation In Disaster Management And Sustainable Tourism - Kusuma Dewi, Dian Suluh (Program Studi Ilmu Pemerintahan Universitas Islam Raden Rahmat Malang, 2024)
Natural disasters are a common occurrence in Indonesia. Disaster management in tourism areas requires planning and government synergy from the national to regional levels. Regulation of the Minister of Tourism and Creative Economy Number 9 of 2021 concerning guidelines for sustainable tourism destinations states that sustainable management standards in destinations must have plans for risk management, crisis management, and emergency response. This study aims to analyze digital innovation steps in the implementation of disaster management in tourism areas. This study uses a qualitative descriptive research method with documentation data collection techniques. The documentation collected is sourced from articles that have been published in reputable international journals Scopus. All the data that has been collected is then analyzed using the help of an analysis tool, namely vosviewer. The study highlights the importance of data-driven decision-making, innovation, and environmental management principles in developing products and services that contribute to economic growth and environmental sustainability. It also emphasizes the need for competitive business models, effective digital leadership, comprehensive digital transformation strategies, and efficient workforce management.